2020
DOI: 10.1590/1519-6984.192140
|View full text |Cite
|
Sign up to set email alerts
|

Germination of chia seeds submitted to saline stress

Abstract: Abstract Salinity, of both soil and water, is one of the main causes of crop yield decline. Within this context, the objective of this study was to evaluate the influence of different salts on the germination of chia seeds. The experiment was conducted in a BOD chamber at a constant temperature of 20 °C and in the presence of light. The seeds were placed on paper soaked with aqueous solutions of calcium chloride (CaCl2), sodium chloride (NaCl), potassium chloride (KCl), and magnesium chloride (MgCl2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Different responses between plant species are reported in the literature regarding pre-treatment in solutions to attenuate salt stress . Soaking increased the germination of Physalis angulata L. (Souza et al, 2016) and chia (Stefanello et al, 2019) seeds, and consequently their salt tolerance. Fredj et al (2013), when evaluating different soaking times (12, 24, and 36h) of coriander seeds in solutions prepared with different NaCl concentrations (0, 2, 4, 6, and 8g L -1 ), reported germination percentage above 90% up to the concentration of 4g L -1 , especially when the seeds were soaked for 12h.…”
Section: Resultsmentioning
confidence: 99%
“…Different responses between plant species are reported in the literature regarding pre-treatment in solutions to attenuate salt stress . Soaking increased the germination of Physalis angulata L. (Souza et al, 2016) and chia (Stefanello et al, 2019) seeds, and consequently their salt tolerance. Fredj et al (2013), when evaluating different soaking times (12, 24, and 36h) of coriander seeds in solutions prepared with different NaCl concentrations (0, 2, 4, 6, and 8g L -1 ), reported germination percentage above 90% up to the concentration of 4g L -1 , especially when the seeds were soaked for 12h.…”
Section: Resultsmentioning
confidence: 99%
“…When evaluating the influence of the salts NaCl, KCl, CaCl 2 and MgCl 2 on the seed germination of chia (Salvia hispanica L. -Lamiaceae), Stefanello et al (2020) concluded that CaCl 2 and MgCl 2 had a negative effect on germination and vigor of seeds when compared to NaCl and KCl. In other words, the chemical differences between these salts can cause changes in the results of germination and vigor of seeds, even when at similar osmotic potentials (Souza & Cardoso, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Literature results show that salinity harms the percentage of the physiological potential of various cultures, such as Oryza sativa L. (CAVALCANTE et al, 2019), Pisum sativum (PEREIRA et al, 2020), Vigna unguiculata L. (GOMES FILHO et al, 2019), and Salvia hispanica (STEFANELLO et al, 2020).…”
Section: Cultivarmentioning
confidence: 99%